2006
DOI: 10.1385/mb:34:1:1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Dopamine D2 Receptor Isoforms Tagged With Green Fluorescent Protein

Abstract: In this study, a cleavable signal peptide fused to the enhanced green fluorescent protein (EGFP) was tagged to the extracellular N-terminus of the human dopamine D2 receptor short and long isoforms (D2S and D2L). Ligand-binding properties of EGFP-tagged receptors were essentially unchanged in comparison to their respective wild-type receptors. The dopamine-mediated activation of both EGFP-D2 isoforms generated a robust inhibition of adenylyl cyclase type 5 in intact cells. In addition, the receptor density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Because single-receptor detection is not yet operational in or ex vivo, we then used high-resolution single-particle detection in cultured hippocampal neurons to investigate the live surface distribution of D1R. To do so, we designed a receptor tagged on its N terminus with a cyan fluorescent protein (D1R-CFP), which does not affect ligand binding nor dopamine-mediated activation (19). No difference was observed when comparing the overall content of D1R in transfected (D1R-CFP) and nontransfected neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because single-receptor detection is not yet operational in or ex vivo, we then used high-resolution single-particle detection in cultured hippocampal neurons to investigate the live surface distribution of D1R. To do so, we designed a receptor tagged on its N terminus with a cyan fluorescent protein (D1R-CFP), which does not affect ligand binding nor dopamine-mediated activation (19). No difference was observed when comparing the overall content of D1R in transfected (D1R-CFP) and nontransfected neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One widely expressed member of the GRK4 subfamily of GRKs, GRK5 (Premont et al, 1995, can regulate D1 and D2 dopamine receptors in cellular model systems (Tiberi et al, 1996;Iwata et al, 1999;Sedaghat et al, 2006). It has also been reported that long-term treatment with cocaine causes an up-regulation of GRK5 mRNA in the septum (Erdtmann-Vourliotis et al, 2001), and significant alterations in expression have been found in experimental PD animals (Ahmed et al, 2008a), suggesting a possible involvement of this kinase in the regulation of receptor responsiveness to dopaminergic drugs.…”
Section: E ␤-Arrestins/g Protein-coupled Receptor Kinases: From Dopamentioning
confidence: 98%
“…G Protein-Coupled Receptor Kinases. GRK2 is widely expressed in the brain, including primary dopaminergic areas (Arriza et al, 1992) and can phosphorylate and regulate D1, D2, and D3 dopamine receptors in in vitro cellular systems (Tiberi et al, 1996;Iwata et al, 1999;Kim et al, 2001;Kabbani et al, 2002;Sedaghat et al, 2006;Banday et al, 2007). Indirect evidence for the role of this kinase in the regulation of dopamine receptors was provided by the observation of alterations in the GRK2 expression levels in the striatum of animals with experimental parkinsonism (Bezard et al, 2005), rats treated with antipsychotics (Ahmed et al, 2008b), and rats receiving long-term cocaine treatment (Schroeder et al, 2009).…”
Section: E ␤-Arrestins/g Protein-coupled Receptor Kinases: From Dopamentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine D 2Sh receptors are localized to the axonal boutons, while dopamine D 2L receptors are localized to the dendrites (Khan et al, 1998). In addition, dopamine D 2Sh receptor isoforms are predominantly localized at the plasma membrane, whereas dopamine D 2L receptor isoforms are found at the cell membrane and within the cell (Sedaghat et al, 2006). Whether cannabinoid hCB 1 receptor variants also have differential localization in distinct neuronal populations is not yet known.…”
Section: Discussionmentioning
confidence: 99%